Long-run in operando NMR to investigate the evolution and degradation of battery cells. Issue 20 (9th May 2018) - Kayser, Steffen A.; Mester, Achim; Mertens, Andreas; Jakes, Peter; Eichel, Rüdiger-A.; Granwehr, Josef
Abstract : On a battery cell running for two months, in operando NMR is demonstrated as a suitable tool to investigate cycling and degradation processes under realistic operating conditions. Abstract : To improve the lifetime of lithium-ion batteries, a detailed understanding of the degradation mechanisms is essential. Nuclear magnetic resonance (NMR) is able to unravel the reversible as well as irreversible transient changes of composition, shape and morphology in a battery cell. Using a newly developed cylindrical battery container free of metallic components in combination with a numerically optimized saddle coil, in operando NMR investigations of battery cells over hundreds of charge/discharge cycles are presented. Alternating with NMR data acquisition, electrochemical impedance spectra (EIS) can be recorded, which enables correlative analysis of the two techniques. Long-run in operando NMR measurements on a Li metal vs. graphite cell reveal the formation and evolution of mossy and dendritic Li microstructures over a period of 1000 h, which illustrates the capabilities of NMR to identify dendrite mitigation strategies in cells operated under realistic conditions.